2021
DOI: 10.3389/fimmu.2020.614363
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: An EGFR-Targeted 4-1BB-agonistic Trimerbody Does Not Induce Hepatotoxicity in Transgenic Mice With Liver Expression of Human EGFR

Abstract: Agonistic monoclonal antibodies (mAbs) targeting the co-stimulatory receptor 4-1BB are among the most effective immunotherapeutic agents across pre-clinical cancer models. However, clinical development of full-length 4-1BB agonistic mAbs, has been hampered by dose-limiting liver toxicity. We have previously developed an EGFR-targeted 4-1BB-agonistic trimerbody (1D8N/CEGa1) that induces potent anti-tumor immunity without systemic toxicity, in immunocompetent mice bearing murine colorectal carcinoma cells expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In addition to those binding domains, they are composed of an additional, third domain that binds to human serum albumin (HSA), which serves the purpose of prolonging the serum half-life of the antibodies (100). Even more, Compte et al have developed a bispecific 4-1BB agonistic Fc-free trimerbody composed of three 4-1BB binding single-chain variable fragments (scFv) and three EGFR binding antibodies for use in cancer treatment (101). By removing the Fc region, the authors sought to enhance the relatively lower efficacy and mitigate off-target toxicities which they attributed to full-length IgG antibodies (101)(102)(103).…”
Section: -1bb In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to those binding domains, they are composed of an additional, third domain that binds to human serum albumin (HSA), which serves the purpose of prolonging the serum half-life of the antibodies (100). Even more, Compte et al have developed a bispecific 4-1BB agonistic Fc-free trimerbody composed of three 4-1BB binding single-chain variable fragments (scFv) and three EGFR binding antibodies for use in cancer treatment (101). By removing the Fc region, the authors sought to enhance the relatively lower efficacy and mitigate off-target toxicities which they attributed to full-length IgG antibodies (101)(102)(103).…”
Section: -1bb In Cancer Immunotherapymentioning
confidence: 99%
“…Even more, Compte et al have developed a bispecific 4-1BB agonistic Fc-free trimerbody composed of three 4-1BB binding single-chain variable fragments (scFv) and three EGFR binding antibodies for use in cancer treatment (101). By removing the Fc region, the authors sought to enhance the relatively lower efficacy and mitigate off-target toxicities which they attributed to full-length IgG antibodies (101)(102)(103). The different takes in the approaches in the design and development of novel, noncanonical antibodies that optimize efficacy while minimizing toxicities are suggestive of the importance and promise of 4-1BB costimulation as a therapeutic strategy.…”
Section: -1bb In Cancer Immunotherapymentioning
confidence: 99%
“…In this study, we generated a small (≈47 kDa) human bispecific costimulatory antibody termed human LiTCo (hLiTCo, li ght T cell co stimulatory ) by fusing the anti-EGFR (human/mouse) EGa1 V HH ( Compte et al., 2020 ) to the N-terminal end of the anti-human 4-1BB SAP3.28 scFv (V H -V L orientation) ( Compte et al., 2021 ) with a flexible GGGGS linker ( Figures 1 , S1 A, and S1B). The hLiTCo-Albu was generated by genetic fusion of the hLiTCo to the N terminus of an albumin sequence with high binding to human FcRn (Albumin HB ) ( Figures 1 , S1 C, and S1D) used previously by ourselves in an Albu-LiTE construct ( Mandrup et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that treatment of immunocompetent transgenic mice expressing huEGFR in the liver (DEGFR-tg) (44) with IgG-based anti-mouse 4-1BB agonist resulted in nonspecific immune stimulation and hepatotoxicity (22). In contrast, none of these features were observed in DEGFR-tg mice treated with the Fcfree EGFR-specific anti-mouse 4-1BB-agonistic 1D8 N/C EGa1 trimerbody ( 22), despite the fact that the anti-EGFR EGa1 V HH recognize huEGFR and moEGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Both trimerbodies were potent costimulators in vitro and the EGFR-targeted 4-1BBagonistic trimerbody showed enhanced tumor penetration and powerful antitumor activity in immunocompetent mice, while alleviating the systemic cytokine production and T-cell-mediated liver toxicities that are associated with IgG-based 4-1BB agonists (15). More recently, we showed in a liver-specific human EGFR-transgenic immunocompetent mouse that systemic administration of anti-4-1BB-agonistic IgGs resulted in nonspecific immune stimulation and hepatotoxicity, whereas in mice treated with the Fc-free EGFR-specific 4-1BBagonistic trimerbody no such immune-related adverse effects were observed (22).…”
Section: Introductionmentioning
confidence: 90%